Minimally invasive transforaminal and anterior lumbar interbody fusion surgery at level L5-S1 - Daniel S. Fidalgo (2020)
This paper presents a finite element analysis to investigate the biomechanical changes caused by transforaminal (TLIF) and anterior lumbar interbody fusion (ALIF) at the L5-S1 level, applying two different implants: T_PAL (TLIF) and SynFix (ALIF). The main objective is to determine which one is more stable for patients. Numerical simulations of segmental motion show that, in the early postoperative phase, displacements and rotation angles obtained in ALIF are greater than the corresponding ones obtained in TLIF, as well as the principal stress values on the ligaments. So, TLIF performed with T_PAL is more stable than ALIF, especially during the recovery phase.